Família, terra e poder oligárquico em Mato Grosso do Sul: legalização do grilo, violência e expropriação indígena no território Terena - LUCIENE MARIA DA SILVA E SILVA (2022)
The intense landholding concentration in Mato Grosso do Sul counterweights the harsh reality experienced by the Indigenous people of the State, whose land recapturing battles happen on a constant basis. If the process of colonization is what causes the outcasting of the originary people from their land, the comprehension of these aspects requires knowledge of occupation proceedings and land domination by the non indigenous and the means to its legitimation. For such, the research has its roots in the Colonial period and the land concession politics, backed by norms set by the Crown and sesmarias. It dedicates itself to the understanding of the State’s political scene, starting from the period when the subject became a matter of the State in order to legislate on landholding matters, analyzing the consequences of the Sesmeiro regime, the Land Laws from 1850 and its concurrent norms.The research also studies, needingly, the identification of the familial components’ presence in strategic public positions in the State of Mato Grosso and Mato Grosso do Sul after its creation, denoting the Oligarchy aspect in the maintenance of power and interest-seeking actions of hegemonic groups. It also attempts to comprehend the role the State plays as a enabler of the territorialization of the capital, as well as other constants, such as the expropriation of the indigenous people from their original land. To do so, the research recognizes the actions of those political agents, from the colonial period to this very day, shining a light on the ideology that shapes the norms and judicial decisions, legitimizing land grabbing in the lands of the State.The fundiary normative set, in both National and State terms (Mato Grosso and Mato Grosso do Sul), was conceived by agrarian oligarchies which, by taking advantage of positions held and their legal competence, have guaranteed the capitalist appropriation of their land, promoting the landholding concentration and the outcasting of the indigenous people, leading to the recapturing movements from those communities.The research also reveals the logic used by the agrarian elites, with their sights pointing at landholding formations and maintenance of an excluding pattern in the distribution of lands in the State. The data with which this research has been made come from the Banco of Teses e Dissertações da CAPES, Banco de Dados da Luta Pela Terra - Dataluta, Comissão Pastoral da Terra, Centro de Trabalho Indigenista, Arquivos do Museu do Índio, Instituto Socioambiental, among others. Keywords: Politics, State, Oligarchies, Land, Indigenous